Investigation of stakeholder prioritization towards organizational financial performance in Malaysia's IT industry - Yi Wen, Beh (2014)
This research discusses about the stakeholder prioritization towards the organizational financial performance. However, to conceptualize the term of stakeholder prioritization, stakeholder orientation was applied. There are four types of stakeholder orientation, which are the employee, customer, competitor and shareholder orientation. Four hypotheses were formed based on the readings of previous reading. Relationships between each type of stakeholder orientation and the organizational financial performance were tested undergoing few analysis. The model was targeted on the finance personnel who has the financial knowledges and able to answer the questionnaire. IT companies which have been recognized as the MSC (Multimedia Super Corridor) status company were selected as the population in this research. The total usable samples of 60 questionnaires were collected through email. SPSS software (version 16.0) was applied to run the factor analysis, reliability analysis, correlation analysis as well as the multiple regression analysis. To have a better understanding on how the respondent companies are doing, their financial performance was evaluated by explaining on the mean score. Next, findings of multiple regression showed that there is positive significant relationship between the employee orientation and the organizational financial performance. However, the rest of the hypotheses (customer, competitor and shareholder orientation) were proven to have no significant relationship towards the organizational financial performance. Finally, the research indicated that the employee should be prioritized foremost as it impacts the financial performance of an organization the most